A Two-step Strategy for High-Value-Added Utilization of Rapeseed Meal by Concurrent Improvement of Phenolic Extraction and Protein Conversion for Microbial Iturin A Production - Wang, Meng; Yang, Chen; François, Jean Marie; Wan, Xia; Deng, Qianchun; Feng, Danyang; Deng, Shiyu; Chen, Shouwen; Huang, Fenghong; Chen, Wenchao; Gong, Yangmin (Frontiers in Bioengineering and Biotechnology, 2021)
Rapeseed meal (RSM) is a major by-product of oil extraction from rapeseed, consists mainly of proteins and phenolic compounds. The use of RSM as protein feedstock for microbial fermentation is always hampered by phenolic compounds, which have antioxidant property with health-promoting benefits but inhibit bacterial growth. However, there is still not any good process that simultaneously improve extraction efficiency of phenolic compounds with conversion efficiency of protein residue into microbial production. Here we established a two-step strategy including fungal pretreatment followed by extraction of phenolic compounds. This could not only increase extraction efficiency and antioxidant property of phenolic compounds by about 2-fold, but also improve conversion efficiency of protein residue into iturin A production by Bacillus amyloliquefaciens CX-20 by about 33%. The antioxidant and antibacterial activities of phenolic extracts were influenced by both total phenolic content and profile, while microbial feedstock value of residue was greatly improved because protein content was increased by ~5% and phenolic content was decreased by ~60%. Moreover, this two-step process resulted in isolating more proteins from RSM, bringing iturin A production to 1.95 g/L. In conclusion, high-value-added and graded utilization of phenolic extract and protein residue from RSM with zero waste is realized by a two-step strategy, which combines both benefits of fungal pretreatment and phenolic extraction procedures.